Police Departments' Use of Facebook: Patterns and Policy Issues. (December 2013) - Lieberman, Joel D.; Koetzle, Deborah; Sakiyama, Mari
Police departments (PDs) are increasingly using social networking sites (SNS) as a method of public communication. Over 75% of the largest U.S. departments currently have a presence on at least one of the three major SNS (i.e., Facebook, Twitter, and MySpace). However, little is known about how departments are actually using these sites. To explore this issue, we conducted a content analysis of messages posted by the 23 largest U.S. PDs using Facebook over a 3-month period. Our results indicate that the content pattern was, to some extent, dependent upon the frequency that departments posted messages. Departments posting more frequently typically used Facebook for crime-related messages, whereas those posting less often were more likely to convey public relations messages. We also identified several message characteristics associated with greater responsiveness on the part of individuals following departments on Facebook. Policy implications of these trends are discussed.